Analisis Life Skill Atlet Petanque Kabupaten Musi Rawas dan Upaya Pengembangannya Melalui Strategi Psikologis - Adika Fatahilah; Syabawaihi; Aditya x Trinanda3 (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
ABSTRACT This study aims to analyze the life skill conditions of Petanque athletes in Musi Rawas Regency and identify aspects that require improvement through psychological strategies, specifically feedback and reinforcement. A quantitative descriptive approach supported by qualitative data from interviews was employed. The research subjects consisted of 35 active Petanque athletes registered under the coaching program of FOPI Musi Rawas Regency. The main instrument used was the Life Skill Inventory, covering dimensions of teamwork, goal setting, time management, emotional skills, interpersonal communication, leadership, problem solving, and decision making. Data were analyzed descriptively using mean scores and percentages, enriched with qualitative interpretations from interviews with coaches and athletes. The results showed that, overall, the life skill level of Petanque athletes in Musi Rawas was in the moderate category (67.3%). The dimensions of goal setting and time management received high scores, while emotional skills and leadership were categorized as low. Interview findings indicated that the limited provision of positive feedback and the absence of a structured reinforcement system from coaches contributed to the weak development of athletes’ psychological aspects. Based on these findings, psychological strategies through the application of feedback and reinforcement are recommended as effective approaches to improving the motivation, discipline, and social skills of Petanque athletes. These findings serve as an important foundation for implementing psychology-based sports coaching programs at the regional level. Keywords: Petanque Athletes, Feedback, Life Skills, Reinforcement, Psychological Strategies